'Chieftaincy' in the Social Media Space: Community Policing in a Twitter Convened Baraza. Issue 1 (5th January 2015) - Omanga, Duncan
Lanet Umoja is on the outskirts of Nakuru town in the Central Rift region, one of the most politically volatile regions in Kenya. Its area chief, Francis Kariuki, has been the focus of local and international media attention for his use of Twitter in transforming the interaction between members of his locale and himself. The focus of this attention has largely been trained on his deployment of the micro blogging platform Twitter for community policing. Using Manuel Castell's idea of the network society and John Postill's concept of how agencies and agents engage a society that is networked, this paper argues that social media has expanded both the spatial and temporal aspects of the baraza, thus producing a very effective site for not only community policing, but also novel experimentation by the chief at the local level.